Quality of life in patients with chronic migraine: relation to migraine severity, depression and sleep disturbances - K. V. Таtаrinova; A. R. Аrtemenko (Нервно-мышечные болезни)
Background. Headache chronification is associated with significant negative impact on health-related quality of life (QOL). Patients with chronic migraine have decreased QOL and increased headache-related disability, than do patients with episodic migraine. The degree to which these outcomes are connected to disease severity, to the pattern of sociodemographic and comorbidity profiles, such as depression, anxiety and sleep disturbances, are unclear.Objective. To assess QOL and to identify predictors of its reduction in patients with chronic migraine.Materials and methods. 160 outpatients with migraine were recruited from a headache center and completed self-report questionnaires including the Headache Impact Test 6 (HIT-6) to assess QOL, Migraine Disability Assessment (MIDAS), Beck depression inventory, Spilberger–Khanin anxiety questionnaire, and Subjective sleep characteristics assessment questionnaire (SSCA). We used multiple regression analyses to obtain QОL predictors and path analysis model to identify relationship between the variables.Results. Patients with chronic migraine (n = 90) had very poor QOL, more severe migraine and comorbid disorders, than did patients with episodic migraine (n = 70). The strongest predictor of the QOL score was the Beck depression inventory score (β = 0.383; p < 0.001) and SSCA questionnaire score (β = –0.341; p < 0.001); followed by the MIDAS score (β = 0.301; p < 0.001), female gender (β = 0.198; p < 0.001), headache intensity (β = 0.173; p < 0.001), attack duration (β = 0.169; p = 0.001), headache frequency (β = 0.150; p = 0.015). Scores of Beck depression inventory, SSCA questionnaire, MIDAS, and headache features (frequency, duration, intensity) had a direct effect on the QOL. Conclusions. Depression and sleep disturbance appear to impair QOL as strong as the severe clinical manifestations of migraine.